(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
One of the causes of skin diseases are bacterial infections, such as Staphylococcus aureus and Staphylococcus epidermidis. Based on previous studies of red ginger (Zingiber officinale Rosc var.rubrum) have antibacterial activity. The aimed of this research was to find the optimum concentration of castor oil and potassium hydroxide (KOH) with good physicochemical properties with Simplex Lattice Design method, and determine the effectiveness of liquid soap against Staphylococcus aureus and Staphylococcus epidermidis with disc diffusion test. Extraction of red ginger with shoxletation and 96% ethanol. The optimization liquid soap design was using Simplex Lattice Design. The basic liquid soap composition was used to predict the optimum formula contain castor oil and KOH for comparasion (0: 100), (25:75), (50:50), (75:25), (100: 0). The research showed optimum consentration value of red ginger ethanol extract is 5%. The optimum formulas contained of 40,035 g of castor oil and 10,875 g KOH. The optimum liquid soap’s colour was brown, charateristic smell of ginger, stiff, with a pH value of 9,4, viscosity of 1233 cP, 1,14% free fatty acids and alkali-free 0%. The independent T test result by using the R-2.14.1 program was p values > 0.05 against S. epidermidis and p <0.05 against S. aureus. As conclusion, the Simplex Lattice Design can produce optimum liquid soap formulas and give antibacterial effectiveness.